(untitled) (International Journal of Engineering and Computer Science, 2017)
Asearch-as-you-type system measures solution on –the-run as a user types the query of keyword, character by character. There emerges a more need to realize support the search-as-you-type on the residing in the relational DBMS. The existing works on the native database SQL, in which the keyword query focusses on to support type of search. The advantage of existing database functionalities is to achieve high performance requirement to attain a high speed. To increases the search performance the auxiliary indexes are used that are stored as tables. But the search as you type for databases are handled only in the single is the main detriment in the existing work at the same way multiple tables were not taken into consideration. The proposed work in which to support multiple tables for search as-you-type in relational database a Fuzzy Multi-join technique is implemented. A Top-K Query Search model is further used to support ranking queries for search as-you-type in the relational database. By using the relational query processors Top-K join queries.